Examination of the relation of localization of placenta at 18-24 weeks of gestation by ultrasonography with the development of preeclampsia later in pregnancy - Pundir, Seema; Namdeo, Neelam; Jain, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of the study was to examine the relation of localization of placenta at 18-24 weeks of gestation by ultrasonography with the development of preeclampsia later in pregnancy. Methods: Hospital based Prospective observational Cohort study at department of Obstetrics and Gynecology, Dr. BSA Hospital Delhi. 150 pregnant women of gestational age18-24 weeks attending ANC clinic were enrolled for ultrasound examination and on the basis of ultrasonography (USG) findings placenta was classified as Group-A (patient found to have laterally located placenta). And Group-B (patients found to have centrally located placenta). All women in both the group were followed up regularly till term. Study duration was 1 year, June 2017-June 2018. Results: The overall risk of developing Preeclampsia with a late rally located placenta was 8.5(odds ratio) with 95% confidence interval (4.0339 to17.9108). This difference was highly statistically significant (p<.0001). Placental laterality has a sensitivity of 77.27%, beside that it has a good specificity of 71.43% and negative predictive value of 80%. Lateral localization of placenta by ultrasonography at mid trimester can be used as a screening test. The presence of urine albumin in group A was found in 70.67% as compared to 13.33% in group B. This difference was statistically significant. (p=0.0001). Around 72% of total complications were seen in Group-A as compared to 28% in Group-B. This difference was found to be statistically significant (p=0.028). Conclusions: Significant correlation exists between placental laterality and the development of preeclampsia and thus placental localization by ultrasonography in midtrimester (at 18-24 weeks) can be used for prediction of development of preeclampsia later in pregnancy.